Casting mold material, method for producing same, method for producing casting mold, and method for regenerating recovered refractory aggregate

By introducing water-soluble inorganic binder and powdered substances containing iron compounds into the mold material, combined with specific treatment methods, the problem of insufficient adhesion and disintegration of the mold material is solved, high strength and good filling properties of the mold are achieved, and regeneration solutions for refractory aggregates are provided.

CN120243824APending Publication Date: 2025-07-04ASAHI YUKIZAI KOGYO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510337597.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-08-03
Filing Date
2018-08-03
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

During the casting process of existing casting materials, the casting materials and/or their cured substances are prone to adhere to the surface of the casting product, resulting in difficulty in subsequent removal and insufficient disintegration of the casting material.

Method used

The mold material containing refractory aggregates, water-soluble inorganic binders and powdered materials containing iron compounds is used to achieve curing by forming a cover layer on the surface of the refractory aggregate and performing water vapor ventilation or heating treatment in the mold to achieve curing, and the refractory aggregate is recovered in combination with magnetic separation and grinding treatment.

Benefits of technology

Effectively suppress the adhesion of the mold material and/or its cured substance to the casting product, improve the strength and fillability of the mold, and can recover regenerated refractory aggregates, reducing labor costs during the regeneration process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120243824A_ABST
    Figure CN120243824A_ABST
Patent Text Reader

Abstract

The invention relates to a casting mold material and a method for manufacturing the same, a method for manufacturing a casting mold, and a method for regenerating recovered refractory aggregate. Provided is a casting material in which adhesion of the casting material and / or a cured product thereof to a cast product is suppressed in a finally obtained mold, and which exhibits excellent mold strength and mold filling properties. The mold material comprises at least (a) a refractory aggregate, (b) a water-soluble inorganic binder, and (c) a powder of an iron-containing compound, and the powder of the iron-containing compound has an average particle diameter of 0.01 [mu] m or more and less than 50 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of August 3, 2018, an application number of 201880048341.2, and an invention title of "Mold Material and Its Manufacturing Method, Mold Manufacturing Method, and Recycling Method for Recycling Refractory Aggregate". Technical Field

[0002] The present invention relates to: a mold material and its manufacturing method, a mold manufacturing method, and a recycling method for recycling refractory aggregate, and particularly relates to: a mold material in which the adhesion of the mold material and / or its cured product to a casting product is suppressed in a finally obtained mold, and which exhibits excellent mold strength and mold filling property. Background Art

[0003] Conventionally, as one of the molds used in the casting of molten metal, the following is used: obtained by using coated sand as a mold material and molding it into a target shape, where the coated sand is formed by covering molding sand formed of refractory aggregate with a prescribed binder. Specifically, in the "Casting Engineering Handbook" edited by the Japan Foundrymen's Society, pages 78 to 90, as such a binder in coated sand, in addition to inorganic binders such as water glass, it is also described that organic binders such as phenolic resin, furan resin, and urethane resin are used, and further, a method of molding a self-hardening mold using these binders is described.

[0004] For example, Patent Document 1 (Japanese Patent Laid-Open No. 2012-76115) describes a binder-coated refractory (coated sand) having good fluidity, which is formed by covering the surface of refractory aggregate with a coating layer of a solid containing a water-soluble inorganic compound such as water glass as a binder. Among them, a method is described in which such a binder-coated refractory (coated sand) is filled into a mold cavity of a molding die for mold molding, and then steam is introduced, whereby the curing of the binder-coated refractory (coated sand) proceeds to obtain a target mold.

[0005] However, as disclosed in Patent Document 1, for conventional coated sand using an inorganic binder such as sodium silicate, since it contains only a trace amount of organic components, the amount of gas generated due to heating accompanied by the injection of molten metal is small. Therefore, during casting, an appropriate gap is not generated between the casting (cast product) and the mold, and there is a concern about the problem of the coated sand (and / or its cured product) adhering to the cast product. Organic binders generally lose their adhesiveness by heating, but inorganic binders do not lose their adhesiveness solely by heating. Therefore, the coated sand (and / or its cured product) adhering to the surface of the cast product often remains on the surface of the cast product even after heating in the casting process and subsequent heat treatment processes. Therefore, after these treatment processes, a process for removing the coated sand (and / or its cured product) adhering to the surface of the cast product is required, and there is a problem of consuming a large amount of labor. In addition, in conventional coated sand using an inorganic binder such as sodium silicate, the collapsibility of the mold obtained by using it is not sufficient, and there is room for improvement in this regard.

[0006] Prior Art Documents

[0007] Patent Documents

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2012-76115

[0009] Non-Patent Documents

[0010] Non-Patent Document 1: "Handbook of Foundry Engineering", pages 78 - 90 Summary of the Invention

[0011] Problems to be Solved by the Invention

[0012] Here, the present invention is made based on the above situation, and the problem to be solved is to provide: a mold material in which the adhesion of the mold material and / or its cured product to the cast product is suppressed in the finally obtained mold, and which exhibits excellent mold strength and mold filling properties. In addition, the problem to be solved by the present invention is also to provide: a method for advantageously manufacturing such an excellent mold material, a method for manufacturing a mold using such an excellent mold material, and further a regeneration method for recovering refractory aggregates.

[0013] Solutions for Solving the Problems

[0014] Moreover, in order to solve the above problems, the present invention can be appropriately implemented in various ways listed below, and in addition, the following-described various ways can be combined arbitrarily. It should be noted that the ways and technical features of the present invention are not limited to the following description, and should be understood as technical solutions that can be recognized based on the inventive concept grasped from the overall description of the specification.

[0015] (1) A mold material, characterized in that it contains at least: (a) a refractory aggregate, (b) a water-soluble inorganic binder, and (c) a powder of an iron-containing compound, and the average particle size of the powder of the iron-containing compound is 0.01 μm or more and less than 50 μm.

[0016] (2) The mold material according to the foregoing aspect (1), wherein the iron-containing compound is an iron oxide.

[0017] (3) The mold material according to the foregoing aspect (2), wherein the iron oxide is selected from the group consisting of magnetite, maghemite, ferrite, and a mixture of two or more of them.

[0018] (4) The mold material according to any one of the foregoing aspects (1) to (3), wherein the powder of the iron-containing compound is contained in a proportion of 1 to 500 parts by mass based on 100 parts by mass of the solid content of the water-soluble inorganic binder.

[0019] (5) The mold material according to any one of the foregoing aspects (1) to (4), wherein when an aqueous solution containing 30% by mass of the water-soluble inorganic binder in terms of solid content is used as a blank solution and the light transmittance at a wavelength of 660 nm of the blank solution is set to 100%, the average value of the light transmittance at a wavelength of 660 nm of a dispersion obtained by mixing 5 parts by mass of the powder of the iron-containing compound with 100 parts by mass of the blank solution is 20% or less.

[0020] (6) The mold material according to any one of the foregoing aspects (1) to (5), wherein the powder of the iron-containing compound is spherical.

[0021] (7) The mold material according to any one of the foregoing aspects (1) to (6), which further contains a surfactant.

[0022] (8) The mold material according to any one of the foregoing aspects (1) to (7), wherein the water-soluble inorganic binder is sodium silicate.

[0023] (9) The mold material according to any one of the foregoing aspects (1) to (8) is dry coated sand having a covering layer containing the water-soluble inorganic binder and the powder of the iron-containing compound formed on the surface of the refractory aggregate and having normal-temperature fluidity.

[0024] (10) The mold material according to any one of the foregoing aspects (1) to (8) is wet coated sand not having normal-temperature fluidity.

[0025] (11) A method for manufacturing a mold material, characterized in that a water-soluble inorganic binder and a powder of an iron compound having an average particle size of 0.01 μm or more and less than 50 μm are added to heated refractory aggregates, and kneaded or mixed to prepare a blend, and the water in the blend is evaporated, thereby manufacturing dry coated sand having a covering layer containing the water-soluble inorganic binder and the powder of the iron compound formed on the surface of the refractory aggregates and having room temperature fluidity.

[0026] (12) The method for manufacturing a mold material according to the foregoing aspect (11), wherein water is further added to prepare the foregoing blend.

[0027] (13) A method for manufacturing a mold material, characterized in that a water-soluble inorganic binder and a powder of an iron compound having an average particle size of 0.01 μm or more and less than 50 μm are added to refractory aggregates, and kneaded or mixed at room temperature, thereby manufacturing wet coated sand.

[0028] (14) The method for manufacturing a mold material according to the foregoing aspect (13), wherein water is added together with the foregoing water-soluble inorganic binder and the powder of the iron compound.

[0029] (15) A method for manufacturing a mold, characterized in that after filling the mold material according to the foregoing aspect (9) into a heated molding die, steam is introduced and held in the molding die to cure or harden it, thereby obtaining a target mold.

[0030] (16) The method for manufacturing a mold according to the foregoing aspect (15), wherein the molding die is heated to a temperature of 80°C to 200°C.

[0031] (17) A method for manufacturing a mold, characterized in that water is added to the mold material according to the foregoing aspect (9) to make it wet, and after filling the wet mold material into a heated molding die, it is held in the molding die to cure or harden it, thereby obtaining a target mold.

[0032] (18) The method for manufacturing a mold according to the foregoing aspect (17), wherein the molding die is heated to a temperature of 80°C to 300°C.

[0033] (19) The method for manufacturing a mold according to any one of the foregoing aspects (15) to (18), wherein during the holding of the molding die, hot air or superheated steam is introduced into the molding die.

[0034] (20) A method for manufacturing a mold, characterized in that after filling the mold material described in the foregoing solution (10) into a heated forming mold, it is held in the forming mold to be cured or hardened, thereby obtaining a target mold.

[0035] (21) The method for manufacturing a mold according to the foregoing solution (20), wherein the forming mold is heated to a temperature of 80°C to 300°C.

[0036] (22) The method for manufacturing a mold according to the foregoing solution (20) or the foregoing solution (21), wherein during the holding of the forming mold, hot air or superheated steam is passed through the forming mold.

[0037] (23) A recycling method for recycling refractory aggregates, characterized in that the recycled refractory aggregates are obtained after casting using a mold formed of the mold material described in any one of the foregoing solutions (1) to (10), and the refractory aggregates contain the water-soluble inorganic binder with the powder containing the foregoing iron-containing compound fixed thereto.

[0038] After recycling the foregoing refractory aggregates, a grinding treatment is performed, and then a magnetic separation treatment is performed. The grinding treatment is to grind the recycled refractory aggregates to scrape off the water-soluble inorganic binder fixed to its surface. The magnetic separation treatment is to separate from the foregoing refractory aggregates the solid matter of the water-soluble inorganic binder scraped off from the refractory aggregates by the action of the powder of the foregoing iron-containing compound contained in the solid matter being attracted by a magnet.

[0039] (24) The recycling method for recycling refractory aggregates according to the foregoing solution (23), characterized in that the magnetic separation treatment is performed using a magnetic separator having a magnetic flux density in the range of 500 to 10,000 gauss.

[0040] (25) The recycling method for recycling refractory aggregates according to the foregoing solution (23) or the foregoing solution (24), characterized in that before the foregoing grinding treatment, between the foregoing grinding treatment and the foregoing magnetic separation treatment, and / or after the foregoing magnetic separation treatment, a roasting treatment is performed on the foregoing refractory aggregates.

[0041] Effects of the Invention

[0042] According to such a mold material of the present invention, its manufacturing method, and the manufacturing method of a mold, various effects can be exerted as listed below.

[0043] (A) In the mold formed of the mold material of the present invention (hereinafter, simply referred to as "mold" in this paragraph), the adhesion of the mold material and / or its cured product to the casting product manufactured using it is effectively suppressed. That is, the powder of the iron-containing compound having an average particle size within a specified range exhibits excellent dispersibility in the water-soluble inorganic binder (and its mixture with water). Therefore, even in the mold formed of the mold material of the present invention, it exists in a good dispersed state, so that the adhesion of the mold material and / or its cured product to the casting product is suppressed, and unevenness does not exist on the outer surface of the casting product.

[0044] (B) The surface roughness of the casting product manufactured using the mold becomes good.

[0045] (C) The mold exhibits excellent strength.

[0046] (D) The fillability in the mold becomes excellent.

[0047] In addition, according to the recycling method of the recycled refractory aggregate of the present invention, various effects described below can be exerted.

[0048] (E) It is possible to easily separate the solid of the water-soluble inorganic binder scraped off by the grinding treatment from the refractory aggregate by magnetic force.

[0049] (F) It is possible to easily separate the solid of the water-soluble inorganic binder that cannot be completely removed by ordinary dust collection operations and adheres by electrostatic action or the like and is scraped off.

[0050] (G) In the solid of the water-soluble inorganic binder scraped off by the grinding treatment, the powder of the iron-containing compound is advantageously present. By subsequent magnetic separation treatment, even the solid of the fine powder can be effectively removed. Therefore, when the recycled refractory aggregate is used to mold the mold again, a decrease in its strength can be advantageously suppressed. Description of the Drawings

[0051] Figure 1 It is a longitudinal sectional view of a sand mold for casting test used to evaluate the adhesion of the coated sand to the casting in the examples.

[0052] Figure 2 It is a longitudinal sectional view of an aluminum alloy casting containing a waste core in the examples. Detailed Description of the Invention

[0053] Therefore, the mold material containing refractory aggregate and water-soluble inorganic binder is classified into a dry-state mold material and a wet-state mold material according to its state after preparation. First, the dry-state mold material refers to a mold material formed by presenting a covering layer formed by a water-soluble inorganic binder on the surface of the refractory aggregate, which has no adhesiveness (does not exhibit adhesiveness) in the dry state, but when water is supplied through ventilation of water vapor or the like, the covering layer (water-soluble inorganic binder) covering the surface of the refractory aggregate dissolves and becomes adhesive. Such a dry-state mold material is, for example, filled into a molding die in a state where adhesiveness is exhibited by adding water, and then heated and dried, or filled into a molding die in the dry state, water is supplied by circulating water vapor or the like in the molding die, and then heated and dried, thereby performing a curing or hardening reaction to form a mold for the molding target. On the other hand, the wet-state mold material refers to a mold material that presents a state where the water-soluble inorganic binder exhibits adhesiveness and is in a wet state (appearance) as a whole. Such a wet-state mold material is, for example, filled into a molding die and heated and dried in the molding die, thereby performing a curing or hardening reaction to form a mold for the molding target. It should be noted that whether the mold material is in a dry state or a wet state is determined according to the water content relative to the solid content of the water-soluble inorganic binder in the mold material, and the water content at which the mold material becomes dry or wet varies depending on the type of the water-soluble inorganic binder. For example, when the water-soluble inorganic binder is water glass, a mold material containing 5 to 55% by mass of water relative to its solid content presents a dry state, while a mold material containing more than 55% by mass of water relative to the solid content of water glass presents a wet state.

[0054] Moreover, the dry-state mold material (coated sand) having normal-temperature fluidity in the present invention refers to a mold material (coated sand) that can obtain a measured value of the dynamic angle of repose regardless of the water content. Here, the dynamic angle of repose is a value obtained by measuring the following angle: The mold material (coated sand) is placed in a cylinder with a transparent single side and a flat surface (for example, the mold material is placed in a container with a diameter of 7.2 cm × a height of 10 cm until half of its volume), and it is rotated at a constant speed (for example, 25 rpm). The slope of the layer of the mold material (coated sand) flowing in the cylinder becomes planar, and the angle formed between the slope and the horizontal plane is measured. This dynamic angle of repose is preferably 80° or less, more preferably 45° or less, and further preferably 30° or less. In particular, when the refractory aggregate is spherical, it is easy to achieve a dynamic angle of repose of 45° or less. On the other hand, the mold material (coated sand) does not flow in the cylinder in a wet state, and the slope of the layer of the mold material (coated sand) does not form a plane, so the dynamic angle of repose cannot be measured. Such a mold material (coated sand) is regarded as a wet-state mold material (coated sand).

[0055] As the refractory aggregate that constitutes the mold material of the present invention, it is a refractory substance that functions as the base material of the mold, and various refractory granular and / or powdery materials that have been used for mold applications can be used. Specifically, starting with silica sand and recycled silica sand, special sands such as alumina sand, olivine sand, zircon sand, chromite sand, etc., slag-based particles such as ferrochrome slag, nickel-iron slag, converter slag, etc., and artificial particles such as alumina-based particles and andalusite-based particles and their recycled particles, and further alumina balls, magnesia clumps, etc. can be cited. It should be noted that these refractory aggregates can be new sand, or can be recycled sand or recovered sand that has been used once or more as foundry sand in mold molding, and further can also be mixed sand obtained by adding new sand to such recycled sand and recovered sand, without limitation. Moreover, such refractory aggregates generally use aggregates with a particle size of about 40 to 130 in terms of the AFS index, and preferably use aggregates with a particle size of about 60 to 110. In addition, the refractory aggregate used in the present invention is preferably spherical. Specifically, ideally, the particle shape coefficient is 1.2 or less, and more preferably 1.0 to 1.1. By using the refractory aggregate with a particle shape coefficient of 1.2 or less, the fluidity and filling property during mold manufacturing become good, and the number of contact points between refractory aggregates increases. Therefore, the amount of water-soluble inorganic binder and additives required to achieve the same strength can be reduced. It should be noted that here, the particle shape coefficient of the refractory aggregate used is generally adopted as a scale showing the external shape of the particle, and is also called the particle shape index, and the closer its value is to 1, the closer it means to a spherical shape (round ball). Moreover, such a particle shape coefficient is expressed by the value calculated using the surface area (sand surface area) of the refractory aggregate measured by various known methods. For example, it refers to the value obtained by measuring the surface area of each 1 g of the actual refractory aggregate particles (sand grains) with a sand surface area measuring instrument (manufactured by Georg Fischer Ltd) and dividing it by the theoretical surface area. It should be noted that the theoretical surface area refers to the surface area when the refractory aggregate particles (sand grains) are all assumed to be spherical.

[0056] In addition, as the water-soluble inorganic binder in the mold material of the present invention, it is advantageous to use a binder mainly composed of one or more substances selected from sodium silicate, sodium chloride, sodium phosphate, sodium vanadate, sodium aluminate, potassium chloride, potassium carbonate, etc. Among them, from the viewpoints of ease of operation, moisture resistance, and finally the strength of the obtained mold, sodium silicate and those mainly composed of sodium silicate are particularly preferred. Here, sodium silicate refers to an aqueous solution of a soluble silicate compound, and examples of such silicate compounds include sodium silicate, potassium silicate, sodium metasilicate, potassium metasilicate, lithium silicate, ammonium silicate, etc. In particular, in the present invention, sodium silicate (sodium silicate) can be advantageously used. In addition, in the present invention, as long as sodium silicate is used as the main component, other water-soluble binders such as thermosetting resins, sugars, proteins, synthetic polymers, salts, and inorganic polymers can also be used. It should be noted that when sodium silicate and other water-soluble binders are used in combination, the proportion of sodium silicate in the total amount of the binder is 60% by mass or more, preferably 80% by mass or more, and more preferably 90% by mass or more.

[0057] Here, sodium silicate is usually classified into types 1 to 5 and used according to the molar ratio of SiO2 / Na2O. Specifically, sodium silicate No. 1 has a molar ratio of SiO2 / Na2O of 2.0 to 2.3, sodium silicate No. 2 has a molar ratio of SiO2 / Na2O of 2.4 to 2.6, and further sodium silicate No. 3 has a molar ratio of SiO2 / Na2O of 2.8 to 3.3. In addition, sodium silicate No. 4 has a molar ratio of SiO2 / Na2O of 3.3 to 3.5, and sodium silicate No. 5 has a molar ratio of SiO2 / Na2O of 3.6 to 3.8. Among them, sodium silicate Nos. 1 to 3 are also specified in JIS-K-1408. Moreover, these sodium silicates can be used alone or in combination, and by mixing two or more sodium silicates, the molar ratio of SiO2 / Na2O can also be prepared.

[0058] It should be noted that, in order to advantageously obtain the mold material of the present invention, for the sodium silicate that constitutes the water glass used as a binder, the molar ratio of SiO2 / Na2O is preferably generally 1.9 or more, more preferably 2.0 or more, and even more preferably 2.1 or more. Among the classifications of the above sodium silicate, sodium silicate corresponding to No. 1 and No. 2 can be particularly advantageously used. The above sodium silicate No. 1 and No. 2 can stably provide a mold material with good characteristics in a wide range of sodium silicate concentrations in the water glass. In addition, the upper limit of the molar ratio of SiO2 / Na2O in such sodium silicate can be appropriately selected according to the characteristics of the water glass in the form of an aqueous solution, generally 3.5 or less, preferably 3.2 or less, and more preferably 2.7 or less. Here, when the molar ratio of SiO2 / Na2O becomes less than 1.9, a large amount of alkali exists in the water glass, so the solubility of the water glass in water increases, and there is a concern that the mold material becomes prone to moisture absorption and deterioration. On the other hand, since the sodium silicate with a molar ratio of SiO2 / Na2O greater than 3.5 has low solubility in water, the bonding area between refractory aggregates cannot be obtained in the finally obtained mold, and there is a concern about the problem of reduced mold strength.

[0059] In addition, the water glass used in the present invention refers to a solution of a silicic acid compound in a water-soluble state. When manufacturing the mold material of the present invention, it can be directly used in the state of the stock solution that can be purchased on the market, or it can also be used in a state diluted by adding water to such a stock solution. Moreover, the non-volatile components (water glass components) obtained by removing volatile substances such as water and solvents from such water glass are called solid components, which correspond to soluble silicic acid compounds such as the above sodium silicate. In addition, the higher the proportion of such solid components, the higher the concentration of the silicic acid compound in the water glass. Therefore, the solid component of the water glass used in the present invention refers to the proportion obtained by removing the water content from the above stock solution when it is composed only of the stock solution. On the other hand, when using a dilution obtained by diluting the stock solution with water, the proportion obtained by removing the water content in the stock solution and the amount of water used in the dilution corresponds to the solid component of the water glass used.

[0060] Moreover, the solid content in such sodium silicate can be set to an appropriate ratio according to the type of sodium silicate component (soluble silicate compound), etc. Preferably, it is advantageously contained in a ratio of 20 to 50% by mass. By kneading or mixing sodium silicate, in which the sodium silicate component corresponding to the solid content is moderately present in an aqueous solution, with a refractory aggregate, an admixture in which the sodium silicate component is uniformly dispersed in the refractory aggregate without unevenness can be prepared. Thus, according to the present invention, a target mold can be advantageously molded. It should be noted that when the concentration of the sodium silicate component (soluble silicate compound) in sodium silicate becomes excessively low and the total amount of the sodium silicate component (solid content) becomes less than 20% by mass, for example, when manufacturing a dry mold material, in order to dry the admixture of the refractory aggregate, the powder of the iron-containing compound, and sodium silicate, it is necessary to increase the heating temperature or extend the heating time. Moreover, for a wet mold material, it is necessary to increase the heating temperature in the molding mold or extend the heating time, thereby causing problems such as energy loss. On the other hand, when the proportion of the solid content in sodium silicate becomes excessively high, it is difficult to prepare an admixture in which the sodium silicate component is uniformly dispersed in the refractory aggregate without unevenness, and problems in the characteristics of the target mold are feared. Therefore, preferably, sodium silicate in the form of an aqueous solution is prepared such that the solid content is 50% by mass or less and thus the water content is 50% by mass or more.

[0061] In the present invention, sodium chloride (NaCl), which can be used as a water-soluble inorganic binder, is edible like table salt, harmless to the human body, inexpensive, and can be easily used. In addition, it is easily soluble in water. Therefore, a mold made of a mold material using sodium chloride as a binder can be made to disintegrate easily in water. In particular, the solubility of sodium chloride in water in the temperature range of 0 to 100 °C is 35.7 to 39.1 g with respect to 100 g of water, and it changes little based on the change in water temperature, so the workability is good. Further, the melting point of sodium chloride is 1413 °C, which is relatively high. Therefore, a mold with high heat resistance can be manufactured.

[0062] In addition, as sodium phosphate, sodium dihydrogen phosphate hydrate (NaH2PO4·xH2O; x is a known integer), disodium hydrogen phosphate hydrate (Na2HPO4·x’H2O; x’ is a known integer), trisodium phosphate hydrate (Na3PO4·x”H2O; x” is a known integer), etc. can be used. Moreover, as represented by the fact that the dissolution amount of trisodium phosphate hydrate with respect to 100 g of water is 1.5 g (0 °C), sodium phosphate is soluble in water. In addition, as represented by the fact that the melting point of disodium hydrogen phosphate hydrate is 1340 °C, the melting point of sodium phosphate is relatively high. Therefore, a mold made of a mold material using sodium phosphate as a water-soluble inorganic binder can be easily disintegrated in water, and a mold with high heat resistance can be manufactured.

[0063] Furthermore, sodium vanadate (Na3VO4) is soluble in water and has a relatively high melting point of 866 °C. Therefore, when using sodium vanadate as a mold material with a water-soluble inorganic binder, the mold is prone to disintegrate in water, and a mold with high heat resistance can be manufactured.

[0064] In addition, sodium aluminate (NaAlO2) is soluble in water and has a melting point of over 1700 °C. Therefore, when using sodium aluminate as a mold material with a water-soluble inorganic binder, the mold is prone to disintegrate in water, and a mold with high heat resistance can be manufactured.

[0065] In addition, potassium chloride (KCl) is easily soluble in water, with a solubility of 28.1 g per 100 g of water at 0 °C, and is inexpensive. It also has a relatively high melting point of 776 °C. Therefore, when using potassium chloride as a mold material with a water-soluble inorganic binder, the mold is prone to disintegrate in water, and a mold with high heat resistance can be manufactured.

[0066] Furthermore, potassium carbonate (K2CO3) is easily soluble in water, with a solubility of 129.4 g per 100 g of water at 0 °C, and has a relatively high melting point of 891 °C. Therefore, when using potassium carbonate as a mold material with a water-soluble inorganic binder, the mold is prone to disintegrate in water, and a mold with high heat resistance can be manufactured.

[0067] Moreover, in the mold material of the present invention, when the above various water-soluble inorganic binders are in solid form, based on their mass, and in liquid form, based on the solid component conversion when only considering the solid components, an amount in a proportion of 0.1 to 5 parts by mass, preferably 0.1 to 2.5 parts by mass, relative to 100 parts by mass of the refractory aggregate can be used. Among them, an amount in a proportion of 0.2 to 2.0 parts by mass can be particularly advantageously adopted. Here, the determination of the solid component is carried out as follows. That is, 10 g of the sample is placed in a sample dish made of aluminum foil (length: 9 cm, width: 9 cm, height: 1.5 cm) and weighed, then placed on a hot plate maintained at 180 ± 1 °C. After 20 minutes, the sample dish is inverted and further placed on the hot plate for 20 minutes. Then, the sample dish is removed from the hot plate, naturally cooled in a desiccator, and weighed. The solid component (mass %) is calculated according to the following formula.

[0068] Solid component (mass %)

[0069] = {[(mass of the dried sample dish (g) - mass of the sample dish (g))

[0070] / (mass of the sample dish before drying (g) - mass of the sample dish (g))}

[0071] × 100

[0072] It should be noted that in the present invention, when the amount of the water-soluble inorganic binder is too small, it is difficult to form a coating layer on the surface of the refractory aggregate in the dry mold material, and there is a concern that the curing or hardening of the mold material may not be sufficient. In addition, in the wet mold material, there is a concern that it is difficult to prepare a mixture (mold material) in which the water-soluble inorganic binder is uniformly dispersed in the refractory aggregate without unevenness. On the other hand, even when the amount of the water-soluble inorganic binder is too large, for the dry mold material, an unnecessary amount of the water-soluble inorganic binder adheres to the surface of the refractory aggregate, and it is difficult to form a uniform coating layer. In addition, for both the dry mold material and the wet mold material, there is a concern that the mold materials may adhere to each other and agglomerate (composite granulation) before mold shaping, which may also cause an adverse effect on the physical properties of the finally obtained mold, and it is difficult to perform shakeout of the core after casting the metal (removal of the cured product of the mold material).

[0073] Moreover, in the mold material of the present invention, together with the above-mentioned water-soluble inorganic binder such as sodium silicate, there is contained a powdery iron-containing compound having an average particle diameter of 0.01 μm or more and less than 50 μm, preferably 0.05 μm or more and 25 μm or less, more preferably 0.1 μm or more and 10 μm or less, and further preferably 0.2 μm or more and 3 μm or less. In this way, the mold material of the present invention contains a powdery iron-containing compound having an average particle diameter within a specified range. Therefore, when casting is performed using a mold formed from the above-mentioned mold material, a proper gap derived from the powdery iron-containing compound is formed between the casting product and the mold, and more specifically, between the casting product and the cured (hardened) binder. Thereby, the adhesion of the mold material and / or its cured product to the casting product is effectively suppressed. In addition, the powdery iron-containing compound having an average particle diameter within a specified range used in the present invention exhibits excellent dispersibility in the water-soluble inorganic binder (and its mixture with water), and the above-mentioned powder also exists in a good dispersed state in the mold formed from the mold material of the present invention. Therefore, the adhesion of the mold material and / or its cured product to the casting product is suppressed, and unevenness does not occur on the outer surface of the casting product. Furthermore, by containing such a powdery iron-containing compound, the thermal conductivity of the mold formed from the mold material of the present invention becomes high, and excellent disintegrability is exhibited during casting. Further, compared with compounds containing other metals, iron-containing compounds are inexpensive and have less influence on the manufacturing cost of the mold material. In addition, since they have excellent thermal conductivity and high specific heat, there is very little concern about causing an adverse effect on the physical properties of the finally obtained mold.

[0074] Here, the iron-containing compound used in the present invention refers to a compound having an iron atom, in other words, all compounds having Fe in the chemical formula. Specifically, iron, ferroalloy, iron oxide, iron oxyhydroxide, iron hydroxide, mixed crystal ferrite in which a part of the iron oxide is replaced by other metals, etc. can be exemplified. In addition, in the present invention, since a powder of an iron-containing compound is used, iron oxide can be advantageously used in consideration of the risks of ignition and explosion. As the iron oxide, ferrous oxide, iron oxide, magnetite (magnetic iron oxide), iron oxyhydroxide, iron hydroxide, maghemite, ferrite, etc. can be exemplified. Among these iron oxides, those having magnetism are particularly preferred. Specifically, magnetite, maghemite, ferrite, and a mixture of two or more of them are particularly preferred. The powder of the iron oxide having magnetism exhibits more excellent dispersibility in a water-soluble inorganic binder (and a mixture with water). Therefore, in the casting product manufactured using the finally obtained mold, the occurrence of orange peel on its surface can be more effectively suppressed. It should be noted that having magnetism means having the ability to adsorb magnetic force.

[0075] In addition, the mold material of the present invention has the following advantages: The regeneration of the refractory aggregate recovered after casting using the mold formed of the above mold material can be advantageously carried out. That is, after casting using the mold formed of the mold material of the present invention, the refractory aggregate with the water-soluble inorganic binder to which the powder of the iron-containing compound is fixed is recovered, and then a grinding treatment is carried out on the recovered refractory aggregate to scrape off the water-soluble inorganic binder fixed on its surface. In the solid of the water-soluble inorganic binder scraped off, the powder of the iron-containing compound is dispersed, and a magnetic separation treatment is carried out to separate it from the refractory aggregate by the action of the powder of the iron-containing compound being attracted by a magnet. Thus, it is possible to more easily separate the solid of the water-soluble inorganic binder scraped off by the grinding treatment from the refractory aggregate by magnetic force, and even more effectively remove the fine powder of the solid of the water-soluble inorganic binder. When the refractory aggregate is regenerated by such a regeneration method, as the iron-containing compound contained in the mold material, magnetic materials such as magnetite, maghemite, ferrite, and a mixture of two or more of them are more preferred.

[0076] In addition, the shape of the powder of the iron-containing compound is not particularly limited, and powders in the shape of spheres, polyhedrons (hexahedrons, octahedrons, etc.), needles, columns, etc. can be used, and spherical powders are preferably used. Among the powders of the iron-containing compound that are spherical, in particular, those having a sphericity of 0.7 or more, preferably 0.8 or more, and more preferably 0.9 or more in terms of the aspect ratio (minor axis / major axis) can be used. Since spherical powders are easily soluble and not easily aggregated, they are easily dispersed in a water-soluble inorganic binder (and a mixture with water), and the fluidity of the admixture also becomes good when producing (preparing) a mold material. It should be noted that the sphericity of the spherical powder refers to the average value of the aspect ratio (ratio of the minor axis to the major axis) obtained from the projected shape by randomly selecting 10 single particles in the observation with a scanning electron microscope.

[0077] Furthermore, the powder of the iron-containing compound used in the present invention desirably has the following characteristics between the water-soluble inorganic binder that constitutes the mold material together with it, in other words, between the water-soluble inorganic binder used simultaneously when producing the mold material. That is, desirably, when an aqueous solution containing 30% by mass of the water-soluble inorganic binder in terms of solid content is used as a blank solution and the transmittance of light at a wavelength of 660 nm is set to 100%, the average value of the transmittance of light at a wavelength of 660 nm of a dispersion obtained by mixing 5 parts by mass of the powder of the iron-containing compound with 100 parts by mass of the above blank solution is 20% or less. More specifically, the transmittance of light at a wavelength of 660 nm of the blank solution (aqueous solution containing 30% by mass of the water-soluble inorganic binder in terms of solid content) is set to 100%, 5 parts by mass of the powder of the iron-containing compound is added to 100 parts by mass of the above blank solution and mixed and stirred to prepare a dispersion. For the dispersion 15 minutes after the above preparation (15 minutes after the end of mixing and stirring), the transmittance of light at a wavelength of 660 nm is measured 3 times with a spectrophotometer. Then, the powder of the iron-containing compound in which the average value of the transmittance of light at a wavelength of 660 nm of the dispersion calculated from the 3 measurement values shows 20% or less, preferably shows 10% or less, is advantageously used in the present invention. The fact that the average value of the transmittance of light at a wavelength of 660 nm of the dispersion is 20% or less means that the powder of the iron-containing compound contained in the dispersion exists in a good dispersed state in the dispersion. Therefore, such a powder of the iron-containing compound also exhibits high dispersibility even in a water-soluble inorganic binder (and / or its aqueous solution).

[0078] It should be noted that, as a method for directly confirming the dispersion state of the powder of the iron-containing compound in the mold, a method of measuring the color difference: ΔE using a color difference meter can be cited. That is, there is a tendency that when the dispersion state of the powder of the iron-containing compound in the mold is poor, the color difference: ΔE value between the mold containing the powder of the iron-containing compound and the mold without the powder of the iron-containing compound becomes low, while when the dispersion state is good, the color difference: ΔE becomes high. Thus, if the color difference: ΔE is 1.0 or more, preferably 2.0 or more, it can be judged that the dispersion state of the powder of the iron-containing compound in the mold is good. For a mold with a good dispersion state of the powder of the iron-containing compound, there are the following advantages: a gap is formed more uniformly between the mold surface and the cast product, the adhesion of the mold material and / or its solidified product to the cast product is more effectively suppressed, and in addition, the reduction in the mold strength caused by the aggregation of the powder of the iron-containing compound is also advantageously suppressed.

[0079] As described above, in order to advantageously enjoy the effects brought about by its compounding, the powder of the iron-containing compound is contained in the mold material of the present invention in an amount such that the ratio is 1 to 500 parts by mass, preferably 10 to 300 parts by mass, and more preferably 20 to 200 parts by mass, relative to 100 parts by mass of the solid content of the water-soluble inorganic binder.

[0080] In addition, in the mold material of the present invention, it is preferable to further contain a surfactant together with the powder of the iron-containing compound. By containing the surfactant, there is an advantage of improving the water permeability in the mold material of the present invention, in other words, the wettability to water. More specifically, for the dry mold material of the present invention containing a surfactant, when water is supplied during mold shaping, the surfactant exists between the supplied water and the water-soluble inorganic binder. Even with a small amount of water, the entire mold material can be effectively wetted, and the following effects can be advantageously enjoyed: 1) The time for supplying water to the mold material (for example, when supplying water by steam, it is the ventilation time of the steam) can be suppressed to the minimum required; in addition, 2) The amount of water supplied to the molding die (molding die cavity) can be suppressed to a small amount, and as a result, the mold after shaping has excellent demoldability from the molding die and also exhibits excellent strength; etc. In addition, for the wet mold material of the present invention containing a surfactant, the following effects can be advantageously enjoyed: 1) By the presence of the surfactant, the amount of water added during its preparation (manufacture) can be suppressed to the minimum required; in addition, 2) The surface tension of water is suppressed, and the fluidity of the mold material is improved; further, 3) The mold after shaping has excellent demoldability from the molding die and also exhibits excellent strength; etc.

[0081] Here, the amount of the surfactant contained in the mold material of the present invention is preferably 0.1 to 20.0 parts by mass, more preferably 0.5 to 15.0 parts by mass, and particularly preferably 0.75 to 12.5 parts by mass with respect to 100 parts by mass of the solid content of the water-soluble inorganic binder. If the amount of the surfactant contained is too small, there is a concern that the above effects cannot be advantageously enjoyed. On the other hand, even if the amount of the surfactant is too large, no improvement in the effect corresponding to the amount used can be confirmed. Moreover, depending on the surfactant, there is a concern that the water-soluble inorganic binder will not solidify during dry state formation, and even if a dry mold material is desired, it cannot be obtained. Furthermore, from the viewpoint of cost performance, it is not a good strategy. In the present invention, as the surfactant, any of a cationic surfactant, anionic surfactant, amphoteric surfactant, nonionic surfactant, silicone-based surfactant, and fluorine-based surfactant can be used.

[0082] Specifically, examples of the cationic surfactant include aliphatic amine salts, aliphatic quaternary ammonium salts, benzalkonium salts, benzethonium chloride, pyridinium salts, imidazoline salts, and the like. In addition, examples of the anionic surfactant include fatty acid soaps, N-acyl-N-methylglycine salts, N-acyl-N-methyl-β-alanine salts, N-acylglutamate salts, alkyl ether carboxylates, acylated peptides, alkyl sulfonates, alkylbenzene sulfonates, alkylnaphthalene sulfonates, dialkyl sulfosuccinate salts, alkyl sulfoglycolates, α-olefin sulfonates, N-acylmethyltaurine, sulfated oils, higher alcohol sulfates, higher secondary alcohol sulfates, alkyl ether sulfates, higher secondary alcohol ethoxysulfates, polyoxyethylene alkylphenyl ether sulfates, monoglyceride sulfates, fatty acid alkanolamide sulfates, alkyl ether phosphate salts, alkyl phosphate salts, and the like. Further, examples of the amphoteric surfactant include carboxybetaine type, sulfobetaine type, amino carboxylates, imidazolinium betaines, and the like. In addition, examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene secondary alcohol ethers, polyoxyethylene alkylphenyl ethers (e.g., Emulgen 911), polyoxyethylene sterol ethers, polyoxyethylene lanolin derivatives, polyoxyethylene polyoxypropylene alkyl ethers (e.g., NEWPOL PE-62), polyoxyethylene glycerol fatty acid esters, polyoxyethylene castor oil, hydrogenated castor oil, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyethylene glycol fatty acid esters, fatty acid monoglycerides, polyglycerol fatty acid esters, sorbitan fatty acid esters, propylene glycol fatty acid esters, sucrose fatty acid esters, fatty acid alkanolamides, polyoxyethylene fatty acid amides, polyoxyethylene alkylamines, alkylamine oxides, acetylene glycols, acetylenic alcohols, and the like.

[0083] In addition, among various surfactants, surfactants having a siloxane structure as a non-polar part are particularly referred to as silicone-based surfactants, and surfactants having a perfluoroalkyl group are referred to as fluorine-based surfactants. Among them, examples of silicone-based surfactants include polyester-modified silicone, acrylic-terminal polyester-modified silicone, polyether-modified silicone, acrylic-terminal polyether-modified silicone, polyglycerol-modified silicone, aminopropyl-modified silicone, and the like. In addition, examples of fluorine-based surfactants include perfluoroalkyl sulfonates, perfluoroalkyl carboxylates, perfluoroalkyl phosphates, perfluoroalkyl trimethyl ammonium salts, perfluoroalkyl ethylene oxide adducts, perfluoroalkyl-containing oligomers, and the like.

[0084] In the present invention, as described above, various surfactants can be used alone or in combination of two or more. Of course, depending on the surfactant, there is a concern that it may react with the water-soluble inorganic binder and the surface activity ability may decrease or disappear over time. Therefore, for example, when water glass is used as the water-soluble inorganic binder, it is advantageous to use an anionic surfactant, a non-ionic surfactant, and a silicone-based surfactant that do not react with the above water glass.

[0085] Furthermore, in the mold material of the present invention, in addition to the above surfactants, various known additives can be appropriately contained as needed. It should be noted that when such additives are contained in the mold material, the following methods can be adopted: a method of premixing a prescribed additive in the water-soluble inorganic binder and then kneading or mixing it with the refractory aggregate; a method of separately adding the prescribed additive and the water-soluble inorganic binder to the refractory aggregate and then uniformly kneading or mixing the whole; and the like.

[0086] As an additive that can be used in the present invention, a moisture resistance improver can be exemplified. In the present invention, any substance can be used as long as it is a moisture resistance improver that has been used in mold materials and does not hinder the effects of the present invention. Specifically, carbonates such as zinc carbonate, basic zinc carbonate, iron carbonate, manganese carbonate, copper carbonate, aluminum carbonate, barium carbonate, magnesium carbonate, calcium carbonate, lithium carbonate, potassium carbonate, and sodium carbonate, borates such as sodium tetraborate, potassium tetraborate, lithium tetraborate, ammonium tetraborate, calcium tetraborate, strontium tetraborate, silver tetraborate, sodium metaborate, potassium metaborate, lithium metaborate, ammonium metaborate, calcium metaborate, silver metaborate, copper metaborate, lead metaborate, and magnesium metaborate, sulfates such as sodium sulfate, potassium sulfate, lithium sulfate, magnesium sulfate, calcium sulfate, strontium sulfate, barium sulfate, titanium sulfate, aluminum sulfate, and zinc sulfate, phosphates such as sodium phosphate, sodium hydrogen phosphate, potassium phosphate, potassium hydrogen phosphate, lithium phosphate, lithium hydrogen phosphate, magnesium phosphate, calcium phosphate, titanium phosphate, aluminum phosphate, and zinc phosphate, hydroxides such as lithium hydroxide, magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, aluminum hydroxide, and zinc hydroxide, oxides of silicon, zinc, magnesium, aluminum, calcium, lithium, copper, iron, boron, zirconium, etc. Among them, especially basic zinc carbonate, sodium tetraborate, potassium metaborate, lithium sulfate, and lithium hydroxide can more favorably improve the moisture resistance when sodium silicate is used as the water-soluble inorganic binder. The moisture resistance improvers represented by the above substances can of course be used alone or in combination of two or more substances. It should be noted that among the compounds listed as moisture resistance improvers above, there are also compounds that can be used as water-soluble inorganic binders. When a different water-soluble inorganic binder is used for the above compounds, they can function as moisture resistance improvers, and when sodium silicate is used as the water-soluble inorganic binder, they can function more effectively as moisture resistance improvers.

[0087] Regarding the dosage of such a moisture resistance improver, relative to the solid content in the water-soluble inorganic binder, it is generally used in a proportion of 0.5 to 10% by mass, preferably 1 to 8% by mass. In order to favorably enjoy the addition effect of the moisture resistance improver, a dosage of 0.5% by mass or more is ideal. On the other hand, if the addition amount is too much, there is a concern about hindering the bonding of the water-soluble inorganic binder and ultimately reducing the strength of the obtained mold. Therefore, a dosage of 10% by mass or less is ideal.

[0088] In addition, in order to improve the disintegration property of the mold, nitrates such as alkali metal nitrates and alkaline earth metal nitrates can be added. Further, in order to improve the moisture retention property of the mold and thicken the water-soluble inorganic binder to improve the demolding property of the mold, polyols, water-soluble high molecular compounds, carbohydrates, sugars, proteins, inorganic compounds, etc. can also be added. As the dosage of such additives, in the total amount, relative to 100 parts by mass of the solid content of sodium silicate, it is generally preferably about 0.5 to 30 parts by mass, among which, more preferably 1 to 20 parts by mass, and particularly further preferably 2 to 15 parts by mass.

[0089] Further, as other additives, it is also effective to contain a coupling agent that strengthens the bonding between the refractory aggregate and the water-soluble inorganic binder. For example, silane coupling agents, zircon coupling agents, titanium coupling agents, etc. can be used. In addition, it is also effective to contain a lubricant that is beneficial to improving the fluidity of the mold material. For example, waxes such as paraffin wax, synthetic polyethylene wax, montanic acid wax, etc.; fatty acid amides such as stearamide, oleamide, erucamide, etc.; alkylene fatty acid amides such as methylene bis-stearamide, ethylene bis-stearamide, etc.; stearic acid, stearyl alcohol; metal stearates such as lead stearate, zinc stearate, calcium stearate, magnesium stearate, etc.; monoglyceryl stearate, stearyl stearate, hydrogenated oil, etc. Further, as a demolding agent, paraffin wax, wax, light oil, machine oil, spindle oil, insulating oil, waste oil, vegetable oil, fatty acid ester, organic acid, graphite particles, mica, vermiculite, fluorine-based demolding agent, silicone-based demolding agent, etc. can also be used. Moreover, these other additives are generally contained in a proportion of 5% by mass or less, preferably 3% by mass or less, relative to the solid content in the water-soluble inorganic binder.

[0090] Therefore, when manufacturing a dry mold material with room-temperature fluidity according to the present invention, the following method can generally be adopted: for the refractory aggregate, an aqueous solution of a water-soluble inorganic binder as a binder is kneaded or mixed together with additives used as required to prepare a mixture in a state where the surface of the refractory aggregate is uniformly covered with the water-soluble inorganic binder. Then, the water contained in the prepared mixture is evaporated (evaporated) to obtain the target dry powdery mold material with room-temperature fluidity (dry coated sand). In the above method, the evaporation of water in the mixture must be carried out rapidly before the solidification or hardening of the water-soluble inorganic binder. Therefore, in the present invention, it is ideal that for the refractory aggregate, after the water-soluble inorganic binder in the form of an aqueous solution is added (mixed), the dry coated sand is formed within 5 minutes, more preferably within 3 minutes, by allowing the water to disperse. This is because if the evaporation time is prolonged, the kneading (mixing) cycle becomes longer and the productivity decreases. In addition, the longer the contact time between the water-soluble inorganic binder and CO2 in the air, the higher the concern about problems such as inactivation. It should be noted that the water content in the dry coated sand thus obtained is prepared such that, for example, when sodium silicate is used as the water-soluble inorganic binder, it becomes 5 to 55% by mass, preferably 10 to 50% by mass, and more preferably 20 to 50% by mass relative to the solid content of sodium silicate.

[0091] In addition, in the manufacturing process of such dry coated sand (molding material), as one of the effective means for rapidly evaporating the moisture in the above-mentioned blend, the following method can be adopted: preheat the refractory aggregate, and knead or mix therein a water-soluble inorganic binder in the form of an aqueous solution to prepare a blend. By kneading or mixing the water-soluble inorganic binder in the form of an aqueous solution in the preheated refractory aggregate, the moisture derived from the water-soluble inorganic binder in the form of an aqueous solution can be extremely rapidly evaporated by the heat of such refractory aggregate. Thus, the moisture content of the obtained molding material can be effectively reduced, and it becomes possible to advantageously obtain dry coated sand having normal-temperature fluidity. It should be noted that the preheating temperature of the refractory aggregate can be appropriately selected according to the type, compounding amount of the water-soluble inorganic binder used, and the moisture content in the aqueous solution of the water-soluble inorganic binder, etc. For example, in the case of sodium silicate, ideally, generally at a temperature of about 100 to 160 °C, preferably about 100 to 140 °C, the refractory aggregate is heated. If the preheating temperature is excessively low, the evaporation of moisture cannot be effectively carried out, and the drying of the blend becomes time-consuming. Therefore, it is ideal to adopt a temperature of 100 °C or higher. Moreover, if the preheating temperature is excessively high, when cooling the obtained coated sand (molding material), the solidification (hardening) of the water-soluble inorganic binder component proceeds, and in addition, composite granulation also occurs. Therefore, there is a concern about problems in the functions of the molding material, especially in physical properties such as strength.

[0092] On the other hand, when manufacturing a wet mold material that does not have fluidity at normal temperature, generally, the following method can be adopted: for refractory aggregates at normal temperature, an aqueous solution of a water-soluble inorganic binder as a binder and additives as required are kneaded or mixed together, so that a wet mold material (coated sand) that does not have fluidity at normal temperature can be obtained. The wet mold material (coated sand) that does not have fluidity at normal temperature is formed by an admixture in a state where the refractory aggregate and the aqueous solution of the water-soluble inorganic binder (and additives) are uniformly mixed. The wet mold material (coated sand) that does not have fluidity at normal temperature is adjusted to a wet state by adjusting its moisture content as required. For example, when using sodium silicate as the water-soluble inorganic binder, the moisture content of the mold material (coated sand) is adjusted to be more than 55% by mass of the solid content of sodium silicate, preferably 70 - 900% by mass, and more preferably 95 - 500% by mass, and then it is manufactured. For the wet mold material (coated sand) whose moisture content has been adjusted in this way, it can be dried by blowing air when filling it into the molding die during mold molding, which can effectively prevent the filling into the molding die from being hindered, and maintain the wetness of the wet mold material (coated sand). Moreover, excellent properties can also be imparted to the mold molded using such a mold material (coated sand). It should be noted that the wet mold material that does not have fluidity at normal temperature in the present invention refers to a mold material for which the dynamic angle of repose cannot be measured regardless of the moisture content.

[0093] It should be noted that the mold material of the present invention can be used in either a dry state or a wet state. By having fluidity at normal temperature, the filling property for the molding die is good, and the operation becomes easier. Therefore, a dry mold material having fluidity at normal temperature is more desirable.

[0094] In addition, in the process of manufacturing the mold material in a dry or wet state, it can be added to the refractory aggregate in a state where a powder containing an iron compound is premixed in an aqueous solution of a water-soluble inorganic binder, and kneaded or mixed. It can also be separately added and kneaded during kneading, or kneaded with a time difference during kneading. Therefore, in the case of the dry mold material of the present invention, the covering layer covering the surface of the refractory aggregate can be composed of a layer in which a water-soluble inorganic binder and a powder of an iron compound are mixed, or can be a structure in which a layer containing a water-soluble inorganic binder and a powder of an iron compound is formed on the outer periphery of the layer formed by the water-soluble inorganic binder. In order to more advantageously enjoy the effects of the present invention, it is ideal that the covering layer covering the surface of the refractory aggregate is a layer in which a water-soluble inorganic binder and a powder of an iron compound are mixed. In addition, a dry substance in which the surface of the refractory aggregate is covered with a covering layer formed by a water-soluble inorganic binder can be manufactured without using a powder of an iron compound. During mold shaping, water, a powder of an iron compound, and other additives as needed are added to the above dry substance and kneaded, and the resulting substance is used as a mold material. It should be noted that when manufacturing the dry or wet mold material of the present invention, in the case where the water-soluble inorganic binder used as the binder is in a solid state, it can be used in a state of being previously dissolved in water. The liquid water-soluble inorganic binder can be used after being diluted with water to adjust its viscosity. In addition, when kneading or mixing with refractory aggregates, etc., a solid or liquid water-soluble inorganic binder and water can also be separately added to the refractory aggregates, etc.

[0095] The method of shaping the target mold using the mold material (coated sand) of the present invention obtained as described above can be classified as follows according to the state of the mold material (coated sand) used, that is, a wet state without normal temperature fluidity or a dry state with normal temperature fluidity.

[0096] When shaping a mold using a wet mold material (coated sand) without normal temperature fluidity, the above mold material is filled into the mold cavity of the molding die that provides the target mold. On the other hand, the molding die is heated to a temperature of 80 to 300 °C, preferably 100 to 200 °C, and maintained in the molding die until the mold material filled therein dries. Through such heating and holding in the molding die, the curing or hardening of the filled mold material proceeds.

[0097] That is, by filling and holding a wet mold material (coated sand) that does not have room-temperature fluidity in the cavity of a heated molding die, the mold material that constitutes the filling phase in the cavity is in a wet state. Therefore, the refractory aggregates are combined and connected with each other by a water-soluble inorganic binder to form an aggregate (combination) of mold materials in an integrated mold shape. It should be noted that if no arbitrary additives are added, the water-soluble inorganic binder is usually cured by evaporation and drying of water. In addition, if oxides or salts are added as hardeners, the water-soluble inorganic binder will harden. The aggregate (combination) of mold materials in the present invention includes any one of those simply cured and those hardened by a hardener. It should be noted that the expression "cured product" in this specification is used to also include the meaning of "hardened product".

[0098] In addition, the wet mold material (coated sand) that does not have room-temperature fluidity is held in a molding die that has been preheated to 80 to 300°C and kept at this temperature for a certain period of time, so as to be dried by evaporation and drying of water and cured or hardened. As the holding temperature based on this preheating, 80 to 300°C can be adopted, preferably 100 to 200°C, more preferably 120 to 180°C. From the reasons of accelerating drying and shortening the molding time and the viewpoint of improving the wet strength by additives, a temperature above 80°C is preferred. From the viewpoint of preventing the occurrence of problems such as the evaporation of moisture before the combination between refractory aggregates is fully formed and the mold strength not being exhibited, a temperature below 300°C is preferred. By heating the molding die at a temperature within such a temperature range, the wet strength of the finally obtained mold can be improved, and the drying of the mold material can be advantageously carried out. It should be noted that in the holding of the mold material in the molding die, in order to promote drying, hot air or superheated steam can be blown into the molding die. In addition, in order to further promote the curing or hardening of the mold material (filling phase), carbon dioxide (CO2 gas), esters, etc. as hardening accelerators can be formed into a gaseous or misty state and aerated in the molding die.

[0099] On the other hand, when molding a mold using a dry mold material (coated sand) with normal-temperature fluidity, as the first method, the dry mold material is kneaded with water at the mold molding site to make it wet, and the wet mold material is preheated to 80 to 300 °C and kept at this temperature for a certain time in the molding cavity of a molding die until the mold material dries. As the holding temperature of the molding die based on preheating in the above first method, 80 to 300 °C can be adopted, preferably 90 to 250 °C, more preferably 100 to 200 °C. As the second method, in the molding cavity of a molding die that has been preheated to 80 to 200 °C and kept at this temperature, a dry mold material is filled, and then steam is blown into the molding cavity to allow the steam to pass through the filling phase formed by the mold material. By this passage of steam, moisture can be supplied to the dry mold material to make it wet, and such a wet mold material is kept in the molding die until it dries. As the holding temperature of the molding die based on preheating in this second method, 80 to 200 °C can be adopted, preferably 90 to 150 °C, more preferably 100 to 140 °C.

[0100] The above first method is carried out as follows: When kneading (mixing) a dry mold material (coated sand) with water, after transporting the dry mold material to the molding site which is the manufacturing place of the mold, water is added at this molding site to make it wet, and then the obtained wet mold material is filled into a molding die to mold the target mold. In this process, the process of wetting the dry mold material by adding water only needs to simply mix the dry mold material with a specified amount of water in a suitable mixer to moisten the mold material. Therefore, it can be implemented with extremely simple operations, and even at a molding site with a poor working environment, it can be carried out extremely simply and easily. It should be noted that when adding water, one or more substances selected from other additives, hardening accelerators, and water-soluble inorganic binders for readjusting the mold strength can be added together. In addition, a substance containing water in the solution can also be used as water.

[0101] In addition, in the above-mentioned second method, when blowing steam into the mold material (filled phase) filled in the molding cavity, the temperature of the steam is generally set to about 80 to 150 °C, and more preferably about 95 to 120 °C. If high-temperature steam is used, a large amount of energy is required for its production. Therefore, a steam temperature near 100 °C can be particularly advantageously used. In addition, according to the present invention, as the pressure of the ventilated steam, in terms of gauge pressure, a value of about 0.01 to 0.3 MPa, more preferably about 0.01 to 0.1 MPa, can be advantageously used. Further, as the ventilation time thereof, a ventilation time of generally about 2 seconds to about 60 seconds can be used. This is because if the ventilation time of the steam is excessively short, it is difficult to sufficiently wet the surface of the dry mold material, and also because if the ventilation time is excessively long, there is a concern about problems such as dissolution and outflow of the water-soluble inorganic binder constituting the surface layer of the mold material (coated sand).

[0102] Here, in the above-mentioned first method and second method, in order to actively dry the filled phase formed by the wetted mold material, the following method can be suitably adopted: blowing hot air or superheated steam into the molding mold and ventilating in the above-mentioned filled phase. By ventilating such hot air or superheated steam (hot air, etc.), it is possible to quickly dry to the inside of the filled phase of the mold material, and it is possible to more advantageously promote the curing or hardening of the above-mentioned filled phase. Thus, it is possible to advantageously increase the hardening speed, and it is also possible to advantageously improve characteristics such as the flexural strength of the obtained mold. In addition, it is also possible to advantageously help shorten the molding time of the mold. In addition, before the ventilation of hot air, etc. in the above-mentioned first method, and between the ventilation of steam and the ventilation of hot air, etc. in the above-mentioned second method, in order to more advantageously promote the curing or hardening of the filled phase, carbon dioxide (CO2 gas), esters, etc. as hardening accelerators can be made to form a gaseous or misty state and ventilated. By neutralizing the water-soluble inorganic binder with such carbon dioxide, esters, etc., it is possible to further promote its curing or hardening. It should be noted that the ventilation of carbon dioxide, esters, etc. can be carried out simultaneously with the ventilation of hot air, etc. in the above-mentioned first method, and can be carried out simultaneously with the ventilation of steam or simultaneously with the ventilation of hot air, etc. in the above-mentioned second method, without limitation.

[0103] It should be noted that examples of the above-mentioned hardening accelerator include esters such as carbon dioxide (carbonated water), methyl formate, ethyl formate, propyl formate, γ-butyrolactone, γ-propiolactone, ethylene glycol diacetate, diethylene glycol diacetate, glycerol diacetate, triacetin, and propylene carbonate; and organic acids such as sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, oxalic acid, carboxylic acid, and p-toluenesulfonic acid, and monohydric alcohols such as methanol, ethanol, butanol, hexanol, and octanol. These hardening accelerators can be used alone or in combination of two or more. It should be noted that for these hardening accelerators, those in a gaseous or mist state can be ventilated in the molding die during the holding of the molding die. In the case of wetting the dry mold material by adding water, the hardening accelerator can also be added together with the mold material and water.

[0104] In addition, as a method for manufacturing a mold using the mold material of the present invention, in addition to the above method, various known modeling techniques can be appropriately adopted. For example, the following layered modeling technique can also be adopted: the layers of the mold material are sequentially stacked, and on the other hand, the part corresponding to the target mold is hardened to directly mold a three-dimensional mold.

[0105] As described above, a specified molten metal is cast using a mold produced by various manufacturing methods to manufacture a target metal component (cast product). As its casting method, there is no particular limitation, and various known casting techniques can be adopted.

[0106] Since the mold material of the present invention contains a powder of an iron-containing compound, for example, the refractory aggregate can be advantageously regenerated by the regeneration method described in detail below. When implementing the regeneration method shown below, after the casting using the mold formed of the mold material of the present invention is completed, the used mold is crushed and / or broken according to a known method using a crusher or the like, and recovered in the form of small pieces, preferably with a size of up to about a few mm or less, and more preferably with a size close to the size of individual grains of the refractory aggregate.

[0107] It should be noted that the main object of the recycling method of refractory aggregates described in detail below is the refractory aggregates recovered from the used molds after casting as described above. However, the object can also be the refractory aggregates recovered in the form of mold materials discharged during the molding process of the mold and the refractory aggregates recovered from unused molds that have never been used for casting. These recycled refractory aggregates all contain a powdery substance containing an iron compound in the water-soluble inorganic binder fixed thereto. Moreover, the refractory aggregates contained in such a water-soluble inorganic binder with a powdery substance containing an iron compound generally constitute the whole or a part of the recycled refractory aggregates to which the recycling method of the present invention is applied, without limitation. In this case, it is present in a proportion of 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more of the recycled refractory aggregates. Needless to say, the higher the proportion of the refractory aggregates containing an iron compound in the recycled refractory aggregates, the more advantageously the features of the present invention can be exhibited. It should be noted that as other refractory aggregates used together with such refractory aggregates containing an iron compound, regardless of whether they contain an iron compound and regardless of the type of the binding component, the refractory aggregates recovered from the mold molding process and the casting process are all the objects thereof.

[0108] Moreover, in the recycling method of the recycled refractory aggregates of the present invention, in order to recycle the recycled refractory aggregates recovered as described above, first, a grinding treatment is performed, and then a magnetic separation treatment is performed. The grinding treatment is to scrape off the solid matter of the water-soluble inorganic binder fixed to the surface of the above-mentioned recycled refractory aggregates, and the magnetic separation treatment is to separate the refractory aggregates from the solid matter scraped off by the force (action) of the powdery substance containing an iron compound contained in the solid matter being attracted by a magnet by magnetic force.

[0109] Among them, the grinding treatment is as follows: The recycled refractory aggregates are ground to scrape off the solid matter of the water-soluble inorganic binder, which is the adherent remaining on the surface of the aggregates, and separate it from the aggregates. Specifically, the recycled refractory aggregates are put into a conventionally well-known grinding device, and the solid binder using a water-soluble inorganic binder such as sodium silicate as the binding component covering or fixing the surface of the aggregates is scraped off. At this time, when the input refractory aggregates are in a lump state, they are broken into individual particles by the rotating rotor of the grinding device and then the surface is further ground. It should be noted that there is no particular limitation on the grinding method in this grinding treatment. For example, a grinding method using a rotary feeder, a sand fresher, a sand shiner, etc. can be appropriately adopted. In addition, the grinding conditions such as the grinding time in the above-mentioned grinding treatment process can be appropriately selected according to the state of fixation of the solid matter on the surface of the aggregates in the recycled refractory aggregates.

[0110] In addition, in the refractory aggregate taken out from the above-mentioned grinding process, there is a mixture of powders of solid matter of the water-soluble inorganic binder scraped off by the grinding process. Moreover, such powders and dust of the binder cannot be sufficiently or reliably removed by a dust collection device or the like usually provided in the grinding device, and physically adhere to the surface of the refractory aggregate. Therefore, in the present invention, the processed material taken out from such a grinding process is further subjected to a magnetic separation process using an appropriate magnetic separator. By utilizing the action (force) that the powder of the iron-containing compound dispersed and contained in the solid water-soluble inorganic binder powder is attracted by the magnet, such powders and dust of the binder are separated from the refractory aggregate. That is, for the grinding processed material in which the refractory aggregate and the solid binder powder are mixed, a magnetic separation process is carried out, so that the refractory aggregate without the adhered binder is recovered to the refractory aggregate recovery section provided below the magnetic separator. On the other hand, the solid binder powder containing the iron-containing compound is recovered to the iron-containing compound recovery section provided below the magnetic separator.

[0111] It should be noted that as the magnetic separator used in the above magnetic separation process, various methods such as the semi-magnetic outer ring method, the suspension method, and the magnetic wheel method are known. As long as the solid binder powder containing the iron-containing compound can be separated from the ground processed material for recovering the refractory aggregate by magnetic force, there is no particular limitation on its structure and form, and a well-known one can be appropriately adopted. In addition, for the magnetic force in such a magnetic separator, in order to separate the refractory aggregate and the solid binder powder containing the iron-containing compound well, ideally, the magnetic flux density is in the range of 500 to 10,000 gauss, preferably 1,000 to 8,000 gauss, and more preferably 1,500 to 6,000 gauss. If the magnetic flux density is lower than 500 gauss, the separation of the binder powder using the magnetic separation process cannot be carried out advantageously. Moreover, if the magnetic flux density becomes higher than 10,000 gauss, the solid binder powder containing the iron-containing compound is strongly attracted by the magnetic separator, resulting in magnetic adsorption, causing problems such as difficulty in its recovery.

[0112] Thus, the mold material of the present invention contains a powder of an iron-containing compound. Therefore, the solid of the water-soluble inorganic binder that adheres to the recycled refractory aggregate necessarily contains the powder of the iron-containing compound. By performing a grinding treatment and a magnetic separation treatment on such recycled refractory aggregate, the solid water-soluble inorganic binder (powder) scraped off by grinding can be easily separated from the refractory aggregate by magnetic force. Moreover, the binder powder of the solid scraped off, which cannot be completely removed only by ordinary dust collection, etc. and adheres to the surface of the refractory aggregate by static electricity, etc., can be easily separated from the aggregate. Based on the above, the recycling method of the recycled refractory aggregate of the present invention can advantageously provide recycled refractory aggregate with good quality. Further, in the refractory aggregate recycled in this way, the solid water-soluble inorganic binder powder scraped off is sufficiently and reliably removed. Therefore, when it is used again for the molding of a mold, a reduction in the strength of the obtained mold can be effectively suppressed, and a mold with excellent strength can be provided.

[0113] Therefore, for the recycling method of the present invention, the operation of performing a calcination treatment for calcining the recycled refractory aggregate that is the object of this recycling can also be advantageously adopted. This calcination treatment can be carried out not only before the grinding treatment of the present invention, but also between such a grinding treatment and a magnetic separation treatment, further after the magnetic separation treatment, and further can be carried out for two or more of before, between, and after these grinding / magnetic separation treatments. It should be noted that in such a calcination treatment of the recycled refractory aggregate, for example, the following method can be adopted: using a calcination furnace such as a rotary kiln or a tunnel kiln, and performing calcination while continuously feeding the recycled refractory aggregate into the calcination furnace.

[0114] It should be noted that when the above-mentioned calcination treatment is carried out before the grinding treatment and the magnetic separation treatment of the present invention, the attachments, dust, and impurities of the refractory aggregate can be burned and removed. As the calcination temperature in the calcination furnace in such a calcination treatment, generally about 200 to 700 °C, preferably about 300 to 700 °C, more preferably about 350 to 650 °C, and further preferably about 400 to 600 °C are adopted. If the calcination temperature becomes lower than 200 °C, there is a concern that the attachments, dust, and impurities of the refractory aggregate cannot be burned sufficiently. Moreover, if the calcination temperature exceeds 700 °C, the following problems will occur: the force of the iron-containing compound attracted by the magnet is reduced due to oxidation, etc., and the water-soluble inorganic binder is sintered, making it difficult to peel off from the refractory aggregate, etc.

[0115] In addition, when the roasting treatment is carried out after the magnetic separation treatment of the present invention, even if the binder temporarily adheres to the recovered refractory aggregate, the water-soluble inorganic binder can be inactivated by the heat of roasting. As the roasting temperature in the roasting furnace in such a roasting treatment, it is generally preferably about 200 to 1000 °C, more preferably about 300 to 900 °C, still more preferably about 350 to 850 °C, and further preferably about 400 °C to 800 °C. If the roasting temperature becomes lower than 200 °C, there is a concern that the water-soluble inorganic binder adhering to the refractory aggregate is not sufficiently inactivated. In addition, if the roasting temperature exceeds 1000 °C, it will cause a load on the roasting furnace and there are concerns about problems such as an increase in heating costs.

[0116] Furthermore, in the method for recycling refractory aggregates of the present invention, it is also effective to further perform a classification treatment on the refractory aggregate product taken out from the grinding treatment or magnetic separation treatment process. When the roasting treatment is carried out after the grinding treatment or magnetic separation treatment of the present invention, the classification treatment is carried out after such a roasting treatment. It should be noted that the above-mentioned classification treatment includes the following processes: a dust collection process in which the refractory aggregate product is made to flow by an air flow, and fine powders contained in such a refractory aggregate product are removed by a dust collection device; and a screening process in which foreign matters contained in the refractory aggregate product are removed by screening. Specifically, in the dust collection process, the refractory aggregate product is made to flow by an air flow, and chips, dust, fine powders and other fine powders contained in the above-mentioned refractory aggregate product that have not been removed in the previous processes are removed by a dust collection device in a driving state. Thus, fine residues can be effectively removed from the refractory aggregate product after grinding or magnetic separation. In addition, in the screening process, the following operation is performed: the particle size of the refractory aggregate product is classified using screening, so as to remove foreign matters contained in such a refractory aggregate product that have not been removed in the previous processes. Thus, large residues can be removed from the refractory aggregate after magnetic separation, and aggregates of an appropriate particle size can be selectively taken out.

[0117] It should be noted that here, the classification treatment adopted is not limited to the dust collection process and the screening process as described above. For example, it may include either the dust collection process or the screening process, without limitation. In addition, the dust collection process may be performed after the screening process, without limitation. Furthermore, as long as the classification process is a method that can classify the refractory aggregates into a specified size, any other known method may also be adopted.

[0118] Moreover, as described above, the refractory aggregates regenerated by the method for recycling refractory aggregates of the present invention can be advantageously used as aggregates (casting sand) that are provided again to the molding process of the mold and can provide a mold with excellent properties.

[0119] It should be noted that the mold materials of the present invention, their manufacturing methods, the manufacturing method of the mold, and the recycling method of the recycled refractory aggregate are not limited by any specific description of the above-described embodiments. It should be understood that the present invention can be implemented in a manner with various changes, modifications, improvements, etc. based on the common knowledge of those skilled in the art, and such embodiments all fall within the protection scope of the present invention as long as they do not depart from the gist of the present invention.

[0120] For example, in each process of the grinding process and the magnetic separation process in the above-described recycling method of the recycled refractory aggregate, since fine powder will fly in the air during the process, in addition to the above-described dust collection process, an operation of sucking the atmosphere can also be appropriately adopted in each process to remove the fine powder.

[0121] Examples

[0122] Hereinafter, several examples of the present invention are shown to further clarify the present invention specifically. Needless to say, the present invention is not limited by any description of these examples. It should be noted that "%" and "parts" shown in the following description are all based on mass unless otherwise specified. In addition, in the following examples and comparative examples, the average particle size of the powder, the light transmittance of the dispersion of the powder, the moisture content of the coated sand (CS) as the mold material, the magnetic adsorption rate of CS, the sand adhesion situation (CS adhesion situation) when casting with each CS, and the surface roughness of the casting surface are measured or evaluated as follows.

[0123] (1) Average particle size of the powder

[0124] For the average particle size of the powder, using a Microtrac particle size distribution measuring device manufactured by Nikkiso Co., Ltd. (product name: MT3200II), the particle size at the cumulative value of 50% of the particle size distribution is used as the average particle size (D 50 ). It should be noted that for the powder used in the examples and comparative examples, the average particle size was measured using the above measuring device, and the error between the result and the announced value of each manufacturer was within 10%. Therefore, hereinafter, the average particle size of the powder shows the announced value of the manufacturer.

[0125] (2) Light transmittance of the dispersion of the powder

[0126] First, for the blank solution formed from an aqueous solution containing 30% by mass of a water-soluble inorganic binder (sodium silicate No. 2 or sodium chloride) in solid content, using a spectrophotometer (manufactured by Hitachi High-Tech Science Corporation, trade name: U-2800), measure the transmittance of light at a wavelength of 660 nm, and adjust this transmittance to 100%. Next, add 5 parts by mass of the powder to 100 parts by mass of the blank solution, stir for 1 minute, and prepare a dispersion. Place the above dispersion in a measuring container, and after standing for 15 minutes, measure the transmittance of light at a wavelength of 660 nm. Conduct the above measurement 3 times, and show the average value of the light transmittance calculated from the measurement values of these 3 times in Tables 1 to 6 below as the "light transmittance of the dispersion".

[0127] (3) Moisture content of CS

[0128] When using sodium silicate as the water-soluble inorganic binder, the moisture content in CS (the moisture content relative to the solid content of the sodium silicate contained in CS) is measured and calculated according to the following steps. In a crucible that has been dried and weighed, weigh 10 g of each CS and place it in the crucible. Using the mass reduction percentage (%) after heating at 900°C for 1 hour, calculate the moisture content (W1) in CS according to the following formula (1). Note that the weighing measurement is accurate to the fourth decimal place. Next, calculate the solid content (B1) of the sodium silicate in CS relative to CS using the following formula (2), and then, based on the moisture content (W1) in CS and the solid content (B1) of the sodium silicate in CS relative to CS, calculate the moisture content relative to the solid content of the sodium silicate (the moisture content of CS relative to the solid content of the sodium silicate in the coating layer: W2) using the following formula (3). Show the W2 calculated as above in Tables 1 to 6 below as the "moisture content".

[0129] W1 = [(M1 - M2) / M3] × 100 ··· (1)

[0130] [W1: Moisture content in CS (%), M1: Total mass of the crucible and CS before roasting (g), M2: Total mass of the crucible and CS after roasting (g), M3: Mass of CS before roasting (g)]

[0131] B1 = [B2 / (100 + B2)] × (100 - W1) ··· (2)

[0132] [B1: Solid content of sodium silicate in CS relative to CS (%), B2: Solid content of sodium silicate added relative to 100 parts of sand (parts), W1: Moisture content in CS (%)]

[0133] W2 = (W1 / B1) × 100 ··· (3)

[0134] [W2: Moisture content (%) of CS relative to the solid content of sodium silicate in the coating, W1: Moisture content (%) of CS, B1: Solid content of sodium silicate relative to CS (%)]

[0135] (4) Magnetic adsorption rate of CS

[0136] For dry CS, 100 g is taken out from CS in the dry state as a sample. On the other hand, for wet CS, after keeping CS in a dryer at 110 °C for 30 minutes, the dried CS is dissolved, and 100 g is taken out from the dissolved substance as a sample. The taken sample is attached to a magnet of 5000 Gauss, and the magnetic adsorption rate of the sample (CS) is calculated from the amount of the sample attached to the magnet according to the following calculation formula.

[0137] Magnetic adsorption rate (%) = [Attached mass (g)] / [Sample amount (g)] × 100

[0138] (5) Evaluation of the adhesion situation of CS

[0139] First, as Figure 1 shown, in a split-type hollow main mold 6 (cavity diameter: 6 cm, height: 6 cm) made of room-temperature self-hardening sand in advance, having a pouring inlet 2 at the upper part and a core seat fixing part 4 with a core at the lower part, after adhesively fixing a circular solid-core mold 10 (diameter: 5 cm, height: 5 cm) with a core seat part 8 made of each CS to the core seat fixing part 4, the split-type hollow main molds 6 are further adhesively fixed to each other to fabricate a sand mold 12 for casting test. Then, aluminum alloy melt (temperature 710 ± 5 °C) is poured from the pouring inlet 2 of the sand mold 12 for casting test, and after it solidifies, the main mold 6 is disintegrated, and Figure 2 the cast object 16 in the shape of a cylinder shown is taken out, and then it reaches room temperature, and with a lathe or the like, the cast object together with the intermediate core is cut in half. After that, the core part is removed, and the adhesion situation of the core sand (CS) to the cast object is visually confirmed. It should be noted that in the present invention, the evaluations of △ and ○ are recorded as qualified. The evaluation results for each CS are shown as "Sand adhesion situation after casting" in Tables 1 to 4.

[0140] ○: No sand adhesion is seen at all.

[0141] △: Sand adhesion is seen in a part of the surface of the cast object.

[0142] ×: Sand adhesion is seen over the entire surface of the cast object.

[0143] (6) Evaluation of the surface roughness of the surface of the cast object

[0144] For the casting in which the sand adhesion condition is confirmed according to the above-mentioned "(5) Evaluation of CS Adhesion Condition", evaluate the surface roughness based on the following criteria according to the visual inspection and the tactile sensation when touching. It should be noted that in the case where sand (CS) adheres to the casting surface, evaluate the surface of the casting after removing the adhered sand (CS) with a brass brush or the like. In the present invention, the evaluations of △ and ○ are recorded as qualified.

[0145] ○: Basically, no unevenness can be visually confirmed, and no catching is felt on the fingertips.

[0146] △: Some unevenness can be visually confirmed, but no catching is felt on the fingertips.

[0147] ×: Large unevenness can be visually confirmed, and catching is felt on the fingertips.

[0148] -Manufacturing Example 1 of Wet CS-

[0149] As the refractory aggregate, prepare commercially available artificial sand for casting, LUNAMOS #60 (trade name, manufactured by Kao Quaker Co., Ltd.). Prepare commercially available sodium silicate No. 2 (trade name, manufactured by Fuji Chemical Co., Ltd., molar ratio of SiO2 / Na2O: 2.5, solid content: 41.3%) as the water glass used as the water-soluble inorganic binder, and prepare a powdery substance of magnetite (spherical, average particle size: 0.25 μm) used as the iron-containing compound. For 100 parts of the aggregate (LUNAMOS #60), an amount equivalent to 1.0 part (solid content: 0.41 part) of water glass, add a powdery substance of magnetite in an amount equivalent to 0.125 part relative to 100 parts of the aggregate (LUNAMOS #60), and mix. After forming a liquid mixture, directly put 100 parts of the aggregate (LUNAMOS #60) into a Shinagawa type universal mixer (5DM-r type, manufactured by DALTON CORPORATION) at normal temperature. Further, put the above-prepared liquid mixture (water glass + powdery substance of magnetite) into the mixer and carry out kneading for 3 minutes, and stir and mix until it becomes uniform. Then, take out the admixture from the mixer to obtain a wet mold material (coated sand): CS1 containing the aggregate, water glass, and powdery substance of magnetite. Calculate the moisture content of the obtained CS1, and the result is an amount equivalent to 140% by mass of the solid content of the water glass.

[0150] -Manufacturing Example 2 of Wet CS-

[0151] Make the addition amount of the powdery substance of magnetite 0.25 part. Except for this, obtain a wet mold material: CS2 according to the same steps as in the above Manufacturing Example 1. Calculate the moisture content of the obtained CS2, and the result is an amount equivalent to 140% by mass of the solid content of the water glass.

[0152] -Manufacturing Example 3 of Wet CS

[0153] The addition amount of the magnetite powder was made 0.50 part. Except for this, according to the same steps as in the above Manufacturing Example 1, a wet mold material: CS3 was obtained. The water content of the obtained CS3 was calculated, and the result was an amount equivalent to 140 mass% of the solid component amount of the water glass.

[0154] -Manufacturing Example 4 of Wet CS

[0155] The addition amount of the magnetite powder was made 1.00 part. Except for this, according to the same steps as in the above Manufacturing Example 1, a wet mold material: CS4 was obtained. The water content of the obtained CS4 was calculated, and the result was an amount equivalent to 140 mass% of the solid component amount of the water glass.

[0156] -Manufacturing Example 5 of Wet CS

[0157] As the magnetite powder, a spherical one with an average particle diameter of 0.10 μm was used. Except for this, according to the same steps as in the above Manufacturing Example 3, a wet mold material: CS5 was obtained. The water content of the obtained CS5 was calculated, and the result was an amount equivalent to 140 mass% of the solid component amount of the water glass.

[0158] -Manufacturing Example 6 of Wet CS

[0159] As the magnetite powder, a spherical one with an average particle diameter of 3.0 μm was used. Except for this, according to the same steps as in the above Manufacturing Example 3, a wet mold material: CS6 was obtained. The water content of the obtained CS6 was calculated, and the result was an amount equivalent to 140 mass% of the solid component amount of the water glass.

[0160] -Manufacturing Example 7 of Wet CS

[0161] As the magnetite powder, an octahedral-shaped one with an average particle diameter of 0.30 μm was used. Except for this, according to the same steps as in the above Manufacturing Example 3, a wet mold material: CS7 was obtained. The water content of the obtained CS7 was calculated, and the result was an amount equivalent to 140 mass% of the solid component amount of the water glass.

[0162] -Manufacturing Example 8 of Wet CS

[0163] The magnetite powder was replaced with a ferrite powder (acicular, average particle diameter: φ0.2×1.0 μm). Except for this, according to the same steps as in the above Manufacturing Example 3, a wet mold material: CS8 was obtained. The water content of the obtained CS8 was calculated, and the result was an amount equivalent to 140 mass% of the solid component amount of the water glass.

[0164] - Manufacturing Example 9 of Wet CS

[0165] Using a powder of iron oxide (acicular, average particle size: φ0.08×0.8 μm) that does not belong to either magnetite or ferrite instead of the powder of magnetite, and following the same steps as in Manufacturing Example 3 above, a wet molding material: CS9 was obtained. The water content of the obtained CS9 was calculated, and the result was an amount equivalent to 140% by mass of the solid content of sodium silicate.

[0166] - Manufacturing Example 10 of Wet CS

[0167] In Manufacturing Example 3 above, a commercially available anionic surfactant (trade name: OLFINE PD-301, manufactured by Nissin Chemical Industry Co., Ltd.) was further added in the proportions shown in Table 2 below. Except for this, following the same steps as in Manufacturing Example 3 above, a wet molding material: CS10 was obtained. The water content of the obtained CS10 was calculated, and the result was an amount equivalent to 140% by mass of the solid content of sodium silicate.

[0168] - Manufacturing Example 11 of Wet CS

[0169] In Manufacturing Example 3 above, a commercially available nonionic surfactant (trade name: OLFINE E1004, manufactured by Nissin Chemical Industry Co., Ltd.) was further added in the proportions shown in Table 2 below. Except for this, following the same steps as in Manufacturing Example 3 above, a wet molding material: CS11 was obtained. The water content of the obtained CS11 was measured, and the result was an amount equivalent to 140% by mass of the solid content of sodium silicate.

[0170] - Manufacturing Example 12 of Wet CS

[0171] Prepare commercially available artificial sand for casting, LUNAMOS#60 (trade name, manufactured by Kao Quaker Co., Ltd.), as a refractory aggregate, prepare a powder of magnetite as an iron-containing compound (spherical, average particle size: 0.25 μm), and further prepare an aqueous sodium chloride solution in which sodium chloride (sodium chloride), used as a water-soluble inorganic binder, is dissolved in water and the solid content (concentration) is 20% by mass. Then, directly put the aggregate (LUNAMOS#60) into a Shinagawa type universal mixer (5DM-r type, manufactured by DALTON CORPORATION) at normal temperature. In the mixer, further add the aqueous sodium chloride solution in a proportion of 3.0 parts (solid content: 0.6 part) relative to 100 parts of the aggregate (LUNAMOS#60), and add the powder of magnetite in a proportion of 0.50 part relative to 100 parts of the aggregate (LUNAMOS#60). Here, the powder of magnetite is added in a state pre-mixed with the aqueous sodium chloride solution. After the above addition, carry out kneading in the mixer for 3 minutes and stir and mix until it becomes uniform. After that, take out the admixture from the mixer to obtain a wet mold material: CS12 containing the aggregate, sodium chloride, and the powder of magnetite. Calculate the moisture content of the obtained CS12, and the result is 79% by mass equivalent to the solid content of the aqueous sodium chloride solution, in other words, the amount equivalent to 79% by mass of the sodium chloride (solid content) contained in CS.

[0172] - Manufacturing Example 13 of Wet CS-

[0173] In the above Manufacturing Example 1, without using the powder of magnetite, and except for this, according to the same steps as in the above Manufacturing Example 1, a wet mold material: CS13 was obtained. Calculate the moisture content of the obtained CS13, and the result is an amount equivalent to 140% by mass of the solid content of the water glass.

[0174] - Manufacturing Example 14 of Wet CS-

[0175] As the powder of magnetite, use the spherical one with an average particle size of 160.2 μm. Except for this, according to the same steps as in the above Manufacturing Example 3, a wet mold material: CS14 was obtained. Calculate the moisture content of the obtained CS14, and the result is an amount equivalent to 140% by mass of the solid content of the water glass.

[0176] - Manufacturing Example 15 of Wet CS-

[0177] As the powder of magnetite, use the spherical one with an average particle size of 106.5 μm. Except for this, according to the same steps as in the above Manufacturing Example 3, a wet mold material: CS15 was obtained. Calculate the moisture content of the obtained CS15, and the result is an amount equivalent to 140% by mass of the solid content of the water glass.

[0178] -Manufacturing Example 16 of Wet CS

[0179] Using a powder of copper oxide (amorphous, average particle size: 32.1 μm) instead of the powder of magnetite, and otherwise following the same steps as in Manufacturing Example 3 above, a wet mold material: CS16 was obtained. The moisture content of the obtained CS16 was calculated, and the result was an amount equivalent to 140% by mass of the solid content of sodium silicate.

[0180] -Molding Example I of Mold (Examples 1 to 12, Comparative Examples 1 to 4)-

[0181] After filling CS1 to 16 (temperature: 20°C) manufactured according to the above respective steps into a molding die heated to 150°C, it was held in the molding die to cure (harden) the CS filled in the above molding die respectively, thereby manufacturing a mold for a test body (φ50×50 cm) used as a circular solid core. It should be noted that the CS used for manufacturing each mold (test body) of Examples 1 to 12 and Comparative Examples 1 to 4 is as shown in Tables 1 and 2 below.

[0182] [Table 1]

[0183]

[0184] [Table 2]

[0185]

[0186] It was clearly confirmed from the results of Tables 1 and 2 above that in the mold obtained by using the wet mold material (CS: coated sand) of the present invention, the adhesion of the mold material (CS: coated sand) to the casting (cast product) manufactured using it was effectively suppressed.

[0187] Next, the dry coated sand (CS) of the present invention was manufactured, and the same test as for the wet CS was carried out.

[0188] -Manufacturing Example 17 of Dry CS

[0189] As a refractory aggregate, commercially available artificial sand for casting, namely LUNAMOS #60 (trade name, manufactured by Kao Quaker Co., Ltd.), was prepared. Commercially available sodium silicate No. 2 (trade name, manufactured by Fuji Chemical Co., Ltd., molar ratio of SiO2 / Na2O: 2.5, solid content: 41.3%) was prepared as the water glass used as a water-soluble inorganic binder, and a powdery substance of magnetite (spherical, average particle size: 0.25 μm) used as an iron-containing compound was prepared. For the water glass in an amount equivalent to 1.0 part (solid content: 0.41 part) relative to 100 parts of the aggregate (LUNAMOS #60), a powdery substance of magnetite in an amount equivalent to 0.50 part relative to 100 parts of the aggregate (LUNAMOS #60) was added and mixed. After forming a liquid mixture, 100 parts of the aggregate (LUNAMOS #60) heated to about 130 °C was put into a vortex mixer (manufactured by Enshu Iron Works Co., Ltd.), and then the above-prepared liquid mixture (water glass + powdery substance of magnetite) was further put into the mixer, and kneaded for 3 minutes to evaporate the water contained in the water glass, and stirred and mixed until the sand grain mass disintegrated. After that, the sand grains were taken out from the mixer to obtain a dry mold material (coated sand): CS17, which had a coating layer containing water glass and a powdery substance of an iron-containing compound formed on the surface of the aggregate. The moisture content of the obtained CS17 was calculated, and the result was an amount equivalent to 32% by mass of the solid content of the water glass in the coating layer.

[0190] - Manufacturing Example 18 of Dry CS

[0191] In the above Manufacturing Example 17, a commercially available anionic surfactant (trade name: OLFINE PD-301, manufactured by Nisshin Chemical Industry Co., Ltd.) was further added in the proportion shown in Table 3 below. Except for this, according to the same steps as in the above Manufacturing Example 17, a dry mold material: CS18 was obtained. The moisture content of the obtained CS18 was calculated, and the result was an amount equivalent to 34% by mass of the solid content of the water glass in the coating layer.

[0192] - Manufacturing Example 19 of Dry CS

[0193] In the above Manufacturing Example 17, the powdery substance of magnetite was not used. Except for this, according to the same steps as in the above Manufacturing Example 17, a dry mold material: CS19 was obtained. The moisture content of the obtained CS19 was calculated, and the result was an amount equivalent to 32% by mass of the solid content of the water glass in the coating layer.

[0194] - Manufacturing Example 20 of Dry CS

[0195] As the powdery magnetite, those in the form of spheres with an average particle diameter of 106.5 μm were used. In addition, following the same steps as in the above Manufacturing Example 17, a dry mold material: CS20 was obtained. The moisture content of the obtained CS20 was calculated, and the result was an amount equivalent to 34% by mass of the solid content of the sodium silicate in the coating layer.

[0196] -Molding Example II of Mold (Examples 13 - 14, Comparative Examples 5 - 6)-

[0197] Under a gauge pressure of 0.3 MPa, CS17 - 20 (temperature: 20°C) manufactured according to the above respective steps was blown into a molding die heated to 110°C. After filling, further under a gauge pressure of 0.05 MPa, steam at a temperature of 99°C was blown for 4 seconds to ventilate the coated sand (CS) phase filled in the molding die. Then, after the ventilation of such steam ended, hot air at a temperature of 150°C was blown under a gauge pressure of 0.03 MPa for 2 minutes to cure (harden) the CS filled in the molding die, thereby manufacturing a mold for a test piece (φ50×50 cm) used as a circular solid core. It should be noted that the CS used for manufacturing each mold (test piece) of Examples 13 - 14 and Comparative Examples 5 - 6 is as shown in Table 3 below.

[0198] [Table 3]

[0199]

[0200] -Molding Example III of Mold (Examples 15 - 16, Comparative Examples 7 - 8)-

[0201] CS17 - 20 (temperature: 20°C) manufactured according to the above respective steps was directly put into a Shinagawa - type universal mixer (Model 5DM - r, manufactured by DALTON CORPORATION) at room temperature, and further water was added to the mixer at a ratio of 1.0 part relative to 100 parts of CS and stirred, thereby preparing wet CS (mold material). The wet CS taken out from the mixer was filled into a molding die heated to 150°C, and then kept in the molding die to cure (harden) the CS filled in the above - mentioned molding die respectively, thereby manufacturing a mold for a test piece (φ50×50 cm) used as a circular solid core. It should be noted that the CS used for manufacturing each mold (test piece) of Examples 15 - 16 and Comparative Examples 7 - 8 is as shown in Table 4 below.

[0202] [Table 4]

[0203]

[0204] It was clearly confirmed from the results of Table 3 and Table 4 above that for the dry mold material (CS: coated sand) of the present invention, when casting is performed using the mold obtained therefrom, the adhesion of the mold material (CS) to the casting (cast product) is also effectively suppressed. In particular, the molds (test specimens) of Examples 13 to 14 were formed from a mold material (CS) humidified by passing steam, and the molds (test specimens) of Examples 15 to 16 were formed from a mold material humidified by adding water. Different molding methods were used in Examples 13 to 14 and Examples 15 to 16, and as a result, it was confirmed that for the molds (test specimens) obtained by any molding method, the adhesion of the mold material (CS) to the casting (cast product) was effectively suppressed.

[0205] -Molding Example IV of Mold (Examples 17 to 18, Comparative Examples 9 to 10)-

[0206] Using CS3, CS7, CS10, CS11, CS13, and CS15, molds (width: 2.54 cm × height: 2.54 cm × length: 20 cm) used as test specimens were produced according to the steps of the above-mentioned "Molding Example I of Mold" respectively. For the obtained molds (test specimens), the flexural strength and the filling rate (%) were measured according to the methods shown below. The measurement results are shown in Table 5 below.

[0207] (7) Flexural strength

[0208] For the molds (test specimens) obtained with each CS, the breaking load was measured using a measuring instrument (manufactured by Takachiho Seiki Co., Ltd.; Digital Casting Sand Strength Testing Machine). Then, using the measured breaking load, the flexural strength was calculated according to the following calculation formula.

[0209] Flexural strength (N / cm 2 ) = 1.5 × (L × W) / (a × b 2 )

[0210] [L: Distance between supports (cm), W: Breaking load (N), a: Width of test specimen (cm), b: Thickness of test specimen (cm)]

[0211] (8) Filling rate

[0212] For the molds (test specimens) obtained with each CS, the ratio of the specific gravity of each mold (test specimen) to the true specific gravity of the aggregate was calculated as a percentage (calculated by dividing the mass by the volume of the test piece).

[0213] Filling rate (mass %)

[0214] ={[Mass of test specimen (g) / Volume of test specimen (cm 3)] / True specific gravity of aggregate (g / cm 3 )}×100

[0215] [Table 5]

[0216]

[0217] It was clearly confirmed from the results in Table 5 that the mold obtained with the mold material of the present invention exhibits excellent mold strength, and in addition, excellent filling properties were also confirmed.

[0218] -Manufacturing examples of recycled CS and molding examples of molds V (Examples 21 to 22, Comparative Example 11)-

[0219] In Figure 1 As shown, inside the split-type hollow main mold 6 (mold cavity: diameter 6 cm × height 6 cm) made of room-temperature self-hardening sand in advance, having a pouring inlet 2 at the upper part and a core seat fixing part 4 with a core at the lower part, the circular solid core 10 (diameter 5 cm × height 5 cm) having a core seat part 8 made of three of the above-mentioned mold materials (CS3, CS10, CS13) respectively was adhesively fixed to the core seat fixing part 4, and then the split-type hollow main molds 6 were adhesively fixed to each other to fabricate a sand mold 12 for casting test. It should be noted that in order to prevent liquid leakage during casting, the bonded main molds were clamped with pliers or the like, or the periphery of the main molds was wound with wire to be firmly fixed. Then, aluminum alloy melt (temperature 710 ± 5 °C) was poured from the pouring inlet 2 of the sand mold 12 for casting test, and after it solidified, the main mold 6 was disintegrated, and the Figure 2 As shown, the cylindrical casting 16 was taken out, and when it reached room temperature, the core was decomposed with a pneumatic hammer, and the mold pieces of the core were recovered. Then, the recovered mold pieces were crushed until their size (maximum length) became 3 mm or less.

[0220] Put 500 parts of the above-mentioned broken mold pieces (refractory aggregate fixed with water glass) into a ball mill as a grinder and perform a grinding treatment for 30 minutes. Then, as a magnetic separation treatment, use a magnet of 5000 Gauss to remove the powdery and granular substances attracted by the magnet from the refractory aggregate after the above-mentioned grinding treatment. After that, as a dust collection process, a dust collector is provided above a 280-mesh sieve, and air is introduced from below during sieving to remove the fine powder components, obtaining the regenerated refractory aggregate. Hereinafter, respectively, 1) Denote the refractory aggregate obtained by regenerating the mold pieces of the core recovered after the above-mentioned casting using the core containing CS3 as regenerated aggregate a; 2) Denote the refractory aggregate obtained by regenerating the mold pieces of the core recovered after the above-mentioned casting using the core containing CS10 as regenerated aggregate b; and 3) Denote the refractory aggregate obtained by regenerating the mold pieces of the core recovered after the above-mentioned casting using the core containing CS13 as regenerated aggregate c. Then, respectively, 1) Use regenerated aggregate a to obtain a wet mold material: regenerated CS3' according to the same manufacturing method as CS3 described above; 2) Use regenerated aggregate b to obtain a wet mold material: regenerated CS10' according to the same manufacturing method as CS10 described above; 3) Use regenerated aggregate c to obtain a wet mold material: regenerated CS13' according to the same manufacturing method as CS13 described above.

[0221] Using the obtained regenerated CS3', regenerated CS10' and regenerated CS13', according to the steps of the above-mentioned "Molding Example I of Mold", make a mold (width: 2.54 cm × height: 2.54 cm × length: 20 cm) for use as a test piece. For the obtained mold (test piece), according to the method shown in the above-mentioned "(7) Measurement of Flexural Strength", measure the flexural strength. Then, based on 1) the flexural strength of CS3 (the flexural strength of Example 17) and the flexural strength of regenerated CS3' obtained using the regenerated aggregate of CS3 (regenerated aggregate a); based on 2) the flexural strength of CS10 (the flexural strength of Example 19) and the flexural strength of regenerated CS10' obtained using the regenerated aggregate of CS10 (regenerated aggregate b); based on 3) the flexural strength of CS13 (the flexural strength of Comparative Example 9) and the flexural strength of regenerated CS13' obtained using the regenerated aggregate of CS13 (regenerated aggregate c), calculate the strength manifestation rate (%) according to the following formula. The results are shown in Table 6 below.

[0222] Strength manifestation rate (%)

[0223] =[Flexural strength of CS (N / cm 2 ) / Flexural strength of regenerated CS (N / cm 2 )] × 100 [Table 6]

[0224]

[0225] It was clearly confirmed from the results in Table 6 above that for the mold materials (recycled CS3', recycled CS10') using the refractory aggregates regenerated from the mold materials of the present invention, the strength manifestation rate was increased (Examples 21-22). In contrast, it was confirmed that for the mold materials (recycled CS13') using the refractory aggregates regenerated from the mold materials obtained by recycling without using the powder containing iron compounds, the strength manifestation rate was low, and it was difficult to efficiently regenerate the recycled refractory aggregates.

[0226] Explanation of Reference Signs

[0227] 2 Molten liquid inlet 4 Core seat fixing part

[0228] 6 Main mold 8 Core seat part

[0229] 10 Circular solid core 12 Casting test mold

[0230] 14 Waste core outlet 16 Casting

Claims

1. A casting mold material, characterized in that, Comprising at least: (a) refractory aggregate, (b) water-soluble inorganic binder, and (c) a powder containing an iron compound, wherein the average particle size of the powder containing the iron compound is 0.01 μm or more and less than 50 μm.

2. The mold material according to claim 1, wherein, The iron compound is an iron oxide.

3. The mold material according to claim 2, wherein, The iron oxide is selected from the group consisting of magnetite, maghemite, ferrite, and a mixture of two or more thereof.

4. The mold material according to any one of claims 1 to 3, wherein, The powder containing the iron compound is contained in a proportion of 1 to 500 parts by mass relative to 100 parts by mass of the solid content of the water-soluble inorganic binder.

5. The mold material according to any one of claims 1 to 4, wherein, When an aqueous solution containing 30% by mass of the water-soluble inorganic binder in terms of solid content is used as a blank solution and the transmittance of light at a wavelength of 660 nm of the blank solution is set to 100%, the average value of the transmittance of light at a wavelength of 660 nm of a dispersion obtained by mixing 5 parts by mass of the powder containing the iron compound with 100 parts by mass of the blank solution is 20% or less.

6. The mold material according to any one of claims 1 to 5, wherein, The powder containing the iron compound is spherical.

7. The mold material according to any one of claims 1 to 6, further containing a surfactant.

8. The mold material according to any one of claims 1 to 7, wherein The water-soluble inorganic binder is sodium silicate.

9. The mold material according to any one of claims 1 to 8, which is dry coated sand having a covering layer containing the water-soluble inorganic binder and the powder containing the iron compound formed on the surface of the refractory aggregate and having normal-temperature fluidity.

10. The mold material according to any one of claims 1 to 8, which is wet coated sand not having normal-temperature fluidity.

11. A method for manufacturing a mold material, characterized in that, A water-soluble inorganic binder and a powder containing an iron compound with an average particle size of 0.01 μm or more and less than 50 μm are added to the heated refractory aggregate, and kneaded or mixed to prepare an admixture, and the moisture in the admixture is evaporated, thereby manufacturing dry coated sand having a covering layer containing the water-soluble inorganic binder and the powder containing the iron compound formed on the surface of the refractory aggregate and having normal-temperature fluidity.

12. The manufacturing method of the mold material according to claim 11, wherein, Water is further added to prepare the admixture.

13. A method for manufacturing a mold material, characterized in that, A water-soluble inorganic binder and a powder containing an iron compound with an average particle size of 0.01 μm or more and less than 50 μm are added to the refractory aggregate, and kneaded or mixed at normal temperature, thereby manufacturing wet coated sand.

14. The manufacturing method of the mold material according to claim 13, wherein, Water is added together with the water-soluble inorganic binder and the powder containing the iron compound.

15. A method for manufacturing a mold, characterized in that, After filling the mold material according to claim 9 into the heated molding die, steam is introduced and held in the molding die to cure or harden it, thereby obtaining a target mold.

16. The manufacturing method of the mold according to claim 15, wherein, The molding die is heated to a temperature of 80°C to 200°C.

17. A method for manufacturing a mold, characterized in that, Water is added to the mold material according to claim 9 to make it wet, and after filling the wet mold material into the heated molding die, it is held in the molding die to cure or harden it, thereby obtaining a target mold.

18. The method for manufacturing a mold according to claim 17, wherein, The molding die is heated to a temperature of 80°C to 300°C.

19. The method for manufacturing a mold according to any one of claims 15 to 18, wherein, During the holding of the molding die, hot air or superheated steam is introduced into the molding die.

20. A method for manufacturing a mold, characterized in that, After filling the molding material according to Claim 10 into the heated molding die, it is held in the molding die to be cured or hardened, thereby obtaining the target mold.

21. The method for manufacturing a mold according to claim 20, wherein, The molding die is heated to a temperature of 80°C to 300°C.

22. The method for manufacturing a mold according to claim 20 or claim 21, wherein, During the holding of the molding die, hot air or superheated steam is passed through the molding die.

23. A recycling method for refractory aggregates, characterized in that, The recycled refractory aggregate is obtained after casting using a mold formed of the molding material according to any one of Claims 1 to 10, and contains the refractory aggregate with the water-soluble inorganic binder to which the powder containing the iron-containing compound is fixed. After recycling the refractory aggregate, a grinding treatment is performed, and then a magnetic separation treatment is performed. The grinding treatment is to grind the recycled refractory aggregate to scrape off the water-soluble inorganic binder fixed to its surface. The magnetic separation treatment is to separate from the refractory aggregate the solid matter of the water-soluble inorganic binder scraped off from the refractory aggregate by the action of the powder of the iron-containing compound contained in the solid matter being attracted by a magnet.

24. The recycling method for recovering refractory aggregates according to claim 23, characterized in that, The magnetic separation treatment is performed using a magnetic separator having a magnetic flux density in the range of 500 to 10,000 gauss.

25. The recycling method for recovering refractory aggregates according to claim 23 or claim 24, characterized in that, Before the grinding treatment, between the grinding treatment and the magnetic separation treatment, and / or after the magnetic separation treatment, a roasting treatment is performed on the refractory aggregate.

Citation Information

Patent Citations

  • Binder-coated refractory, casting mold, method for producing the casting mold

    JP2012076115A